Hubungan Antara Sikap Humanis Dengan Hasil Belajar IPS Siswa Kelas IV SD - Awaluddin Muin; Sitti Jauhar; Heriani Rahman; Mujahidah Mujahidah (Universtas Negeri Makassar, 2022)
The purpose of this study is to determine whether there is a significant relationship between humanist attitudes and social studies learning outcomes for fourth grade elementary school students in cluster I. This type of research is a descriptive quantitative research with correlational model. The results showed that there was a significant relationship between humanist attitudes and social studies learning outcomes for fourth graders of SD Cluster I. The tcount value was 2,294 which was greater than ttable, so the alternative hypothesis H1 was accepted while H0 was rejected. Based on the results of this study, it can be concluded that there is a significant relationship between humanist attitudes and social studies learning outcomes for fourth grade students of SD Cluster I. The impact of this research is that it is known that there is a contribution given by a humanist attitude to social studies learning outcomes for fourth grade students of SD Cluster. I.